Extracardiac conduit in total cavopulmonary connection - Paulista,Paulo Paredes (2003)
OBJECTIVE: This study evaluates a new technique of an extracardiac conduit in total cavopulmonary connection in complex congenital heart disease. METHODS: Between May 2000 and October 2002, 18 extracardiac conduit surgeries were performed. The patients' weights ranged from 11 to 29 kilograms, the ages ranged from 1 to 12 years old and 10 patients were male. There were eight patients with tricuspid atresia, eight with univentricular heart, and two with unbalanced total atrioventricular septal defect. There were 17 patients who had been submitted to a previous palliative surgery. The surgery was performed at over 32º centigrade without aortic ischemia. Ten PTFE, 4 Hemashield and 4 bovine pericardium tubes were used with diameters ranging from 16 to 22 mm. RESULTS: There were four cases of tube thrombosis and these patients were a reoperation was performed with one death. In one patient a takedown was performed on the 69th postoperative day. There were three deaths, one due to tube thrombosis and two due to low cardiac output. CONCLUSION: Extracardiac conduit is already used for total cavopulmonary connection, but despite encouraging early results, a longer follow-up is necessary to prove its real advantages.